Nationalismi ja kieli (Finnish Literature Society / SKS, 2025)
This book looks at the relationship between nationalism and language through a theoretical introduction and case studies focusing on Eastern Europe, the Middle East, Africa, and Asia. It encourages readers to reflect on language-related phenomena and their own language attitudes – and at the same time reconsider concepts such as “mother tongue” and “national language” that guide language policies and debates on language issues. The scholarly knowledge of the history of language, language learning, the relationship between language and the production of knowledge that the authors highlight is often at odds with how nationalist narratives frame the status of language and guide language policies and education. The book is useful for students and professionals working with language: language teachers, researchers, language planning authorities and experts in multilingualism. It provides food for thought for all those interested in the relationship between language and society.